2019
DOI: 10.1016/j.ijscr.2019.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A case report of an adjustable gastric band erosion and migration into the jejunum resulting in biliary obstruction

Abstract: HighlightsLAGB can rarely erode into the stomach and migrate into the small bowel.Migration of the LAGB can result in bowel and biliary obstruction.Band erosion should be managed by removal of the LAGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Twelve papers did not meet the selection criteria. Forty-three [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] case reports were eventually included in our review ( Figure 1 ). The first report was published in 2000, while other articles were written last year.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers did not meet the selection criteria. Forty-three [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] case reports were eventually included in our review ( Figure 1 ). The first report was published in 2000, while other articles were written last year.…”
Section: Resultsmentioning
confidence: 99%
“…Erosion and migration of the band within the digestive lumen is one of the less frequent late complications occurring after LAGB, [9] . Moreover, migration is generally limited to the stomach and cases with distal dislocation of the band have been only a matter of case reports [10] , [11] , [12] , [13] , [14] or description of cases within case series [15] , [16] . Life threatening presentations of such distal migration of the band causing gastro-intestinal injuries are very rare [15] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case reported by Shah et al [10] , a migrated and dislocated band occluded the jejunum with associated duodenum wall thickening and signs of pancreatitis. Nasser et al [14] has reported a case of biliary dilation with a narrowing of the lower bile duct likely secondary to compression from the tubing of a migrated band into the jejunum. The same mechanism on the papilla may be advocated in the present case in which however a rod like effect of the tube of the gastric band was extended to the pancreas as was revealed by the exploration of the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die häufigste Lokalisation der Perforation ist der proximale Magen, wie in ▶ Abb. 1 a gezeigt, es sind aber auch Perforationen in den Ösophagus oder die Dislokation bis in das Jejunum beschrieben [7,8,9,10]. Die Indikation zur Entfernung des Magenbandes besteht somit auch bei einer oligosymptomatischen Erosion.…”
Section: Die Magenbandperforationunclassified